(untitled) (Economic and Political Thought, 2012)
The author presumes that the basic pre-causes of the world financial crisis should be looked for in macroeconomics. In 1980s, its mainstream, embracing classical liberalism modified by J.M. Keynes and – to certain degree – by ordoliberalism (sometimes improperly included into the neoliberal path), was pushed out and replaced by the Hayek-Friedman neoliberal doctrine. That doctrine was transformed step by step into an ideology causing an essential deformation of macroeconomics and neglecting the role of scientific premises in shaping the world economy. The author argues that neoliberalism was based on the false dogma of self-regulation and self-stabilizing capabilities of not only individual free market but also inter-market links within any free market economy as a whole. The economic policy based on that doctrine led to harmful consequences, particularly on the financial markets taken out from the system of proper regulations and empowered with the features of supra-state bodies. The mixture of the Austrian school anti-state vision and the Chicago school’s hypothesis of rational expectations has brought about improper interventionism as well as malfunctioning of the market mechanisms. The results of that type opened a way for the most radical libertarian vision of anarcho-capitalism, leading to a complete elimination of the state not only from the economy but also from the political and social life of the nations. According to the author, an implementation of this vision would mean a catastrophe to individual countries but, first of all, to the European Union as the organization integrating not only markets but also the state institutions as their regulators. Under these circumstances the author advocates looking for new systemic solutions and a new scientific doctrine for economic policy, suggesting synergic liberalism, based on the permanent joint action of the states and markets in order to achieve synergy effects going beyond the results of their complementarities or typical interventionism.